2013
DOI: 10.1161/circulationaha.112.127639
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Value of the Preoperative Echocardiogram to Predict Mortality and Major Morbidity in Coronary Artery Bypass Surgery

Abstract: Background— Although echocardiography is commonly performed before coronary artery bypass surgery, there has yet to be a study examining the incremental prognostic value of a complete echocardiogram. Methods and Results— Patients undergoing isolated coronary artery bypass surgery at 2 hospitals were divided into derivation and validation cohorts. A panel of quantitative echocardiographic parameters was measured. Clinical variables were extracted from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 49 publications
2
35
0
1
Order By: Relevance
“…In the current study, as in our previous study of patients undergoing isolated CABG,7 measures of LV diastolic dysfunction and RV dysfunction emerged as the main incremental predictors of postoperative outcomes. Moreover, measures of LV remodeling and low mean aortic gradient emerged as strong predictors of postoperative outcomes in the setting of SAVR, reflecting the deleterious effect of this phenotypic response to chronic pressure overload.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In the current study, as in our previous study of patients undergoing isolated CABG,7 measures of LV diastolic dysfunction and RV dysfunction emerged as the main incremental predictors of postoperative outcomes. Moreover, measures of LV remodeling and low mean aortic gradient emerged as strong predictors of postoperative outcomes in the setting of SAVR, reflecting the deleterious effect of this phenotypic response to chronic pressure overload.…”
Section: Discussionsupporting
confidence: 69%
“…This represents a missed opportunity to enhance risk prediction given the wealth of hemodynamic, functional, and structural data available in routinely performed preoperative echocardiograms. Recently, our group demonstrated the incremental prognostic value of preoperative echocardiograms in patients undergoing isolated CABG 7. Thus, we expanded this hypothesis to patients undergoing SAVR to determine the incremental prognostic value of the echocardiogram in addition to the STS risk score to predict short‐ and long‐term mortality and major morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion criteria were (1) coronary artery bypass graft surgery (CABG), valve repair or replacement surgery, or combined CABG plus valve surgery performed during the study timeframe; (2) case captured by the STS Adult Cardiac Surgery Database for the Boston sites or by the Pre-Operative Surgical Stratification by Echocardiography (POSSE) database for the Montreal site 9 ; and (3) age ≥50 years at the time of surgery. Elective, urgent, and emergent surgeries were included.…”
Section: Participantsmentioning
confidence: 99%
“…11 Afilao et al observed preoperative RV dysfunction and restrictive LV filling as powerful predictors of mortality or major morbidity after CABG, whereas RV dysfunction and pulmonary hypertension predicted long-term mortality over 3.2 years. 16 The right ventricle fractional area change has found to be predictive of inotropes requirement and ventilator hours in early postoperative period in patients with severe LV dysfunction undergoing CABG. 17 Longitudinal strain incrementally improves the risk stratification of both valvular and CABG surgery patients obtained even with the recently proposed Euro-SCORE II.…”
Section: Discussion-mentioning
confidence: 98%